Caregiver role strain: bi-national study of content validation - Rueda Diaz, Leidy Johanna; Lopes Monteiro da Cruz, Diná de Almeida; de Cassia Gengo e Silva, Rita (Investigación y Educación en Enfermería, 2016)
Objective. To estimate content validity of the diagnosis Caregiver Role Strain. Methods. Content validation of the defining characteristics according to Fehring’s model was undertaken by 6 Colombian nurses and 9 Brazilian counterparts. The relevance of each defining characteristic for the diagnosis was assessed using 5-point Likert type scale. The Mann-Whitney test was used to estimate differences in assessing the relevance of defining characteristics between Brazilian and Colombian nurses. Results. From 36 defining characteristics, 22 were identified as major, 13 as secondary and one as irrelevant (rash). The content validity index (sum of weighted averages divided by the total number of defining characteristics) was 0.79, considered adequate. Conclusion. Most of the defining characteristics were considered relevant to the nursing diagnosis Caregiver Role Strain. These findings reflect consensus among specialists from two different countries in relation to the relevance of the defining characteristics for this diagnosis. How to cite this article: Rueda LJ, Cruz DALM, Silva RCG. Caregiver role strain: bi-national study of content validation. Invest. Educ. Enferm. 2016; 34(2):